STATUS OF TORPEDO SCAD (MEGALASPIS CORDYLA) FISHERIES IN THE PALABUHANRATU BAY - Septiyaningsih, Anis; Noviyanti, Rinda; Panggabean, Donwill; Nazzla, Rauzatul (Universitas Mataram, 2025)
Data and information explain that the catch of small pelagic species including Tetengkek in the waters of the Indian Ocean has decreased (Sadhotomo & Atmaja, 2012), the total catch of Tetengkek in 2023 is 1,126 tons, down 60% compared to the total catch in 2019 (BPS, 2024). This information is an early indication that small pelagic fishery resources are getting closer to over-fishing and in the future will become a problem for the livelihoods of fishermen, including fishermen in Palabuhanratu Bay. This study aims to determine the status of Torpedo Scad fish (Megalaspis cordyla) in Palabuhanratu Bay based on catches landed at the Palabuhanratu Nusantara Fisheries Port and to recommend the management of Torpedo Scad fish resources with an ecosystem approach. The ecosystem approach is based on two of the six domains of the Ecosystem Approach to Fisheries Management (EAFM), namely the domains of fish resources, and fishing technology. A multi-criteria analysis was performed on the composite index for each of EAFM indicators. Furthermore, measures and recommendations for resource management are formulated based on the objectives of the EAFM. The results of the study show that the status of Scad torpedo fish management in Palabuhanratu Bay is generally